Validation studies of Y-chromosome short tandem repeats for forensic applications - Delfin, Frederick C (2003)
Y-chromosome short tandem repeats (Y-STRs) are valued for their applicability in forensic cases such as sexual assault that require the identification of a male DNA source. The most widely used Y-STR system known as the minimal haplotype is composed of eight Y-STR markers, namely DYS19, DYS3891, DYS38911, DYS390, DYS391, DYS392, DYS393 and DYS385. To be able to apply forensic DNA typing procedures using Y-STR minimal haplotype in the Philippines, the effectiveness of the system must first be evaluated in-house. Internal laboratory validation for the local Y-STR typing procedure wad performed in a single locus DNA amplification and slab gel fragment analysis format. Validation was facilitated by s Y-STR haplotyping quality assurance exercise in collaboration with the Institut fur Rechtsmedizin, Humboldt-Universitat, Berlin, Germany where 100 % concordance of typing results and contribution of Philippine Y-STR haplotype population data standardized the local Y-STR typing procedure with those validated by the European DNA profiling group. The local Y-STRs' inherent specificity for male DNA was demonstrated by reproducible Y-STR results for DNA from different forensic samples such as blood and buccal cells which are standard samples for human identification and paternity testing, human tissue (e.g. heart, kidney, liver, umbilical tissue and bone) which may be recovered from mass disasters and male-female cell mixtures found on vaginal swabs which are common sexual assault evidence. The same results demonstrated the system's compatibility with the various DNA extraction procedures used in the study. Autosomal STR loci HUMTHO1 and HUMvWA were initially used to evaluate purified DNA in terms of quality and to complement Y-STR typing results. THe reliability, reproducibility and robustness of the Y-STR typing procedure was demonstrated by consistent results generated from each sample after repeated analyses. With autosomal STR system currently in place in our laboratory, the validated Y-STR typing procedure will augment the laboratory's capability for forensic casework, particularly for sexual assault where male DNA detection and identification will aid in the objective resolution of cases.